EDUKASI GIZI PADA IBU BALITA TENTANG MANFAAT NUTRISI IKAN UNTUK PENCEGAHAN STUNTING - Rosnah Rosnah; Rofiqoh Rofiqoh; Purnomo Leksono; Imanuddin Imanuddin; Teguh Faturrahman; Syaifudin Suhri Kasim (Jurnal Pengabdian NUSANTARA, 2022)
The purpose of this writing is to find out about Nutrition Education For Toddlers Mothers About The Benefits Of Fish Nutrition To Prevent Stunting. This community service activity uses the counseling method with the help of leaflet media, followed by the practice of processing fish-based food (nuggets and croquettes). Evaluation of activities using a questionnaire containing stunting, complementary food for breast milk (MPASI), and variations in fish processing. The questionnaire was filled in twice, namely before and after counseling. Data processing using SPSS, statistical analysis dependent T test (α <0.05) to see an increase in knowledge. The evaluation results showed that the average value of knowledge of mothers under five before counseling was 6.1, with the lowest score being 4 and the highest being 8. After counseling, there was an increase in the mean value of knowledge significantly different (p = 0.000), namely being 9.7, with the lowest value being 9 and the highest is 10. Counseling with the help of leaflet media accompanied by the practice of processing fish-based food is proven to be effective in increasing knowledge of mothers of toddlers about the nutritional benefits of fish for stunting prevention.